An Intelligent Job Scheduling System for Web Service in Cloud Computing - Jing Liu; Xing Guo Luo; Bai Nan Li; Xing Ming Zhang; Fan Zhang (Institute of Advanced Engineering and Science, 2013)
Cloud computing is a new computing and business paradigm with flexible and powerful computational architecture to offer universal services to users via Internet. Web service is one of the most active and widely adopted implementation in cloud computing. The performance of the scheduling system influences the benefits of both sides in this computing paradigm. In this paper, we present an intelligent scheduling system for web service, which considers both the requirements of different service requests and the circumstances of the computing infrastructure which consists of various resources. We have validated our hardware based server WSVP by conducting a performance comparison to the traditional Apache and Nginx servers. The results demonstrate that our WSVP equipped with intelligent scheduling system has immense potential as it offers better performance while consumes much lower energy.DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2118